Banking relationships : evidence from Portuguese SMEs - Carneiro, Jorge Fernando Giesteira (2021)
Firstly, the purpose of this master thesis is to investigate which determinants might influence the Portuguese small and medium enterprise’s (SMEs) decision to have multiple banking relationships, instead of a single one. Secondly, verify if these determinants will produce the same effect in a situation, where the firms have already multiple banks, but pretend to increase even more their number of banking relationships. Despite existing already multiple studies, that establish which factors might affect the number of banking relationships, few of them separate these two different situations in which a firm can be ex-ante. Considering a sample of 8714 firms, it was concluded that the interbank competition and the level of risk of the lender and the borrower affect the firm´s source of financing decisions. On the other hand, the “Hold- Up Problem” does not show any signals of affecting firm´s source of financing decisions. Furthermore, the impact of these determinants shows to be the same, independently, if the firm has one or multiple banking relationships, ex-ante.